Optimization of episomal reprogramming for generation of human induced pluripotent stem cells from fibroblasts - Bang, Jin Seok (Anim Cells Syst (Seoul), 2018)
Generation of induced pluripotent stem cells (iPSCs) by defined factors (OCT4, SOX2, C-MYC, and KLF4) from various human primary cells has been reported. Human fibroblasts have been widely used as a cellular source in reprogramming studies over recent decades. The original method of iPSC generation uses retro- or lentivirus vectors that require integration of viral DNA into the target cells. The integration of exogenous genes encoding transcription factors (OCT4, SOX2, C-MYC, and KLF4) can be detected in iPSCs, raising concern about the risk of mutagenesis and tumor formation. Therefore, stem cell therapy would ideally require generation of integration-free iPSCs using non-integration gene delivery system such as Sendai virus, recombinant proteins, synthetic mRNA, and episomal vectors. Several groups have reported that episomal vectors are capable of reprogramming human fibroblasts into iPSCs. Although vector concentration and cell density are important in the episomal vector reprogramming method, optimization of this method for human fibroblasts has not been reported. In this study, we determined optimal conditions for generating integration-free iPSCs from human fibroblasts through the use of different concentrations of episomal vectors (OCT4/p53, SOX2/KLF4, L-MYC/LIN28A) and different plating cell density. We found that optimized vector concentration and cell density accelerate reprogramming and improve iPSC generation. Our study provides a detailed stepwise protocol for improved generation of integration-free iPSCs from human fibroblasts by transfection with episomal vectors.